Viral RNA intermediates as targets for detection and discovery of novel and emerging mosquito-borne viruses. - Caitlin A O'Brien; Jody Hobson-Peters; Alice Wei Yee Yam; Agathe M G Colmant; Breeanna J McLean; Natalie A Prow; Daniel Watterson; Sonja Hall-Mendelin; David Warrilow; Mah-Lee Ng; Alexander A Khromykh; Roy A Hall (Public Library of Science (PLoS), 2015)
Mosquito-borne viruses encompass a range of virus families, comprising a number of significant human pathogens (e.g., dengue viruses, West Nile virus, Chikungunya virus). Virulent strains of these viruses are continually evolving and expanding their geographic range, thus rapid and sensitive screening assays are required to detect emerging viruses and monitor their prevalence and spread in mosquito populations. Double-stranded RNA (dsRNA) is produced during the replication of many of these viruses as either an intermediate in RNA replication (e.g., flaviviruses, togaviruses) or the double-stranded RNA genome (e.g., reoviruses). Detection and discovery of novel viruses from field and clinical samples usually relies on recognition of antigens or nucleotide sequences conserved within a virus genus or family. However, due to the wide antigenic and genetic variation within and between viral families, many novel or divergent species can be overlooked by these approaches. We have developed two monoclonal antibodies (mAbs) which show co-localised staining with proteins involved in viral RNA replication in immunofluorescence assay (IFA), suggesting specific reactivity to viral dsRNA. By assessing binding against a panel of synthetic dsRNA molecules, we have shown that these mAbs recognise dsRNA greater than 30 base pairs in length in a sequence-independent manner. IFA and enzyme-linked immunosorbent assay (ELISA) were employed to demonstrate detection of a panel of RNA viruses from several families, in a range of cell types. These mAbs, termed monoclonal antibodies to viral RNA intermediates in cells (MAVRIC), have now been incorporated into a high-throughput, economical ELISA-based screening system for the detection and discovery of viruses from mosquito populations. Our results have demonstrated that this simple system enables the efficient detection and isolation of a range of known and novel viruses in cells inoculated with field-caught mosquito samples, and represents a rapid, sequence-independent, and cost-effective approach to virus discovery.